Two Case Reports on Thalamic and Basal Ganglia Involvement in Children with Dengue Fever - Guwani Liyanage; Lihini Adhikari; Saraji Wijesekera; Maheshaka Wijayawardena; Suchithra Chandrasiri (Case Reports in Infectious Diseases)
There have been increasing numbers of case reports of dengue infection with unusual manifestations. Such unusual manifestations including acute liver failure and encephalopathy could be manifested even in the absence of significant plasma leakage. Further, severe organ involvement including nervous system involvement indicates severe dengue infection. However, neurological manifestations of dengue fever are rare. This is the first case report of dengue infection with thalamic and basal ganglia involvement in Sri Lanka.